Alterations of human immune system functions in relation to environmental contamination, gender and alcohol consumption intensity - Kazbariene, Birute; Kalibatas, Julius; Krikstaponiene, Aurelija; Zabulyte, Danguole (Central European Journal of Public Health, 2007)
Environmental contamination and use of alcohol may be a cause of immune system disturbances and various diseases. The aim of this study was to evaluate changes of different alcohol consumption intensity on the immune condition of women and men living in a district contaminated with industrial siftings (Trakai) and in a relatively clean district (Širvintos). The immune system parameters were investigated in 282 Trakai district inhabitants (127 males and 155 females) and in 282 Širvintos district inhabitants (129 males and 153 females). Due to gender and alcohol consumption intensity the immune system functions were evaluated in the following groups: abstainers, light alcohol users, moderate alcohol users and alcohol abusers. Absolute number of CD5+, CD4+, concentration of IgA in blood serum and some other investigated indices of light alcohol users were signifi cantly increased in the male group of Trakai district in comparison with females of this district. However, in the same group of light alcohol drinkers of Širvintos district, males had lower indices (CD5+, CD4+, CD4+/CD8+, IgM) than females. Immune system parameters of males who were light and moderate alcohol users in Trakai district were stimulated in comparison with the same alcohol consumption groups of males in Širvintos district. Our investigations showed that combination of environmental pollution and different intensity of alcohol consumption cause various alterations of immune system functions in males and females.
Keywords: Immune System Diseases; Sex Distribution; Alcoholism; znečištění životního prostředí; nemoci imunitního systému; lidé; alkoholismus; Data Interpretation, Statistical; Lithuania; rozložení podle pohlaví; interpretace statistických dat; Litva; odběr vzorku krve; Blood Specimen Collection; Environmental Pollution; Humans